تحضير مبعثرات صلبة للترامادول هيدروكلوريد بطريقة التجفيف بالإرذاذ - إبراهيم, وهاد (Latakia University Journal -Medical Sciences Series, 2018)
Tramadol Hydorchloride is a centrally acting analgesic, which often used for the treatment of chronic and acute pain. However it has a short half life and should be taken many times a day. Therefore, slow release preparation seem to be a logical approach to improve the patient compliance. The aim of this study was to prepare a solid dispersion of Tramadol-HCl with Ethyl cellulose (EC) using spray drying technique. We investigated the impact of the Drug/polymer-Proportion on each of the yield, entrapment efficiency (EE) and the physical state of the solid dispersion. The DSC results reveal the crystalline trace of tramadol-HCl until the 1:7 portion was accessed. There was no clear influence either on the yield nor on the EE. الترامادول هيدروكلوريد هو مسكن ألم مركزي يستخدم بكثرة في الحالات الحادة والمزمنة إلا أن عمره النصفي القصير يستدعي تكرار الجرعة عدة مرات ومن هنا تأتي ضرورة إيجاد شكل مطول التحرر لتحسين مطاوعة المريض. هدفت هذه الدراسة إلى تحضير مبعثر صلب لمادة الترامادول هيدروكلوريد Tramadol.HCl باستخدام الايتيل سللوز EC كحامل وذلك بطريقة التجفيف بالإرذاذSpray drying . تمَ التحري عن تأثير نسبة المادة الفعالة إلى السواغ (ترامادول هيدروكلوريد /إيتيل سللوز) على كل من نسبة الحفظ ومحصول التجفيف وعلى الحالة الفيزيائية للمبعثر الصلب. أظهرت نتائج المسعر الحراري DSC بقاء نسبة من الترامادول بشكل بلوري ضمن المبعثر الصلبة حتى الوصول إلى نسبة 1/7 التي ظهر عندها التوزع الأمورفي للمادة الدوائية ضمن الإيتيل سللوز. أما محصول التجفيف ونسبة الحفظ فلم يتأثرا بنسبة المادة الفعالة إلى السواغ.